(untitled) (Latakia University Journal -Medical Sciences Series, 2016)
أجريت الدراسة في مشفى الأسد الجامعي باللاذقية , في قسم التوليد وأمراض النساء في الفترة الممتدة بين 1/1/2013 وحتى 1/1/2014 وكان عدد مريضات الدراسة 190 حالة بينها 140 حالة تم اجراء تسليخ الأغشية لها و50 حالة دون تسليخ الأغشية. • وقد أجري تسليخ للأغشية عند مريضات الدراسة ,وذلك بعد تقييم درجة نضج عنق الرحم اعتماداً على مشعر بيشوب وكانت نسبة الاستجابة 79.28% في حالات تسليخ الأغشية وهي النسبة الأعلى ,ثم 54%في الحالات دون تسليخ الأغشية. وكان إجراء التسليخ لمرتين متتاليتين كافياً عند أغلب المريضات, وكان عنق الرحم متوسط النضج (أي درجة 4-5 حسب مشعر بيشوب )هو الأكثر استجابة لإجراء التسليخ. • وكانت نسبة الولادة الطبيعية في دراستنا 87.85% في حالات تسليخ الأغشية و 76% دون تسليخ الأغشية. • وقد كانت الاختلاطات محدودة جداً في مجموعة الدراسة وشملت : 1-الإنتان 0.58%. 2-النزف 0.58%. 3-انبثاق الأغشية 1.16%. أي أن تسليخ الأغشية كان إجراءاً آمناً إلى حد ما. This study was made at ALASSAD Hospital-TISHREEN University in-LATTAKIA at the Department of Obestetrics and Gynecology in the period between 1/1/2013 and 1/1/2014. The number of patients the study was 190.Including140 cases have been holding membrane stripping and 50 cases without membrane stripping. According to Bishop –Scoring index we have estimated the uterine cervix in patients, then a Membrane- Stripping was made. Rate of response was 79.28% in cases of membrane stripping "then 54%in cases " without membrane striping ". In most cases of response ,we need to do the membrane stripping twice.Top of response was obtained when Bishop –Scoring index was between 4-6 (Moderate ripening of the cervix). Rate of Vaginal Delivery was 87.85% in cases of membrane stripping and 76% without membrane stripping. The complications were limited in the study group included: 1-Infection( 0.58%). 2-Bleeding 0.58%. 3-PROM 1.16%. It means that Membrane Stripping was somehow safe.